How to establish electronic, scholarly, open access and peer-reviewed journal in small country - Trajkovski, Vladimir (Alma Mater Europaea - ECM, 2022)
Introduction: publishing an electronic, peer-reviewed, open-access academic journal in a small country is really hard work. The advancement of electronic journals during recent years has given professionals in academia a powerful new tool to support learning and research. The purpose of this article is to provide some guidelines about creating electronic, scholarly, open access and peer-reviewed journal in small country through the example of Journal of Health and Rehabilitation Sciences. Methods: An analysis of relevant literature, sources from the Internet and published literature, personal experience and observations of the author as editor-in-chief in two similar journals previously. Findings: a new modern academic journal should be open access, peer-reviewed, with international editorial board, having staff who work very dedicatedly. The journal should be set it up on OJS platform, using Creative Commons license for authors and DOI numbers for the articles. Plagiarism detection is a prevention of publication ethics violation. Journal editors should make additional efforts to index journal in lot of scholarly databases and to intend to increase the visibility. Sharing journal content on social media has become an important instrument and platform for editors and researchers as well. Conclusions: Journal of Health and Rehabilitation Sciences (JHRS) is a multidisciplinary peer reviewed, international, electronic journal. Editorial office expects your submitted articles in the following weeks and months.
Keywords: electronic, scholarly, open access, peer-review, journal, JHRS, small country